Preribosomes escaping from the nucleus are caught during translation by cytoplasmic quality control - Sarkar, Anshuk; Thoms, Matthias; Barrio García, Clara; Thomson, Emma; Flemming, Dirk; Hurt, Ed (Nature structural & molecular biology, 2017)
Assembly of fully functional ribosomes is a prerequisite for failsafe translation. This explains why maturing preribosomal subunits have to pass through an array of quality-control checkpoints, including nuclear export, to ensure that only properly assembled ribosomes engage in translation. Despite these safeguards, we found that nuclear pre-60S particles unable to remove a transient structure composed of ITS2 pre-rRNA and associated assembly factors, termed the 'foot', escape to the cytoplasm, where they can join with mature 40S subunits to catalyze protein synthesis. However, cells harboring these abnormal ribosomes show translation defects indicated by the formation of 80S ribosomes poised with pre-60S subunits carrying tRNAs in trapped hybrid states. To overcome this translational stress, the cytoplasmic surveillance machineries RQC and Ski-exosome target these malfunctioning ribosomes. Thus, pre-60S subunits that escape nuclear quality control can enter translation, but are caught by cytoplasmic surveillance mechanisms.